2019
DOI: 10.1128/jcm.01336-18
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Plasma from Whole Blood by Use of the cobas Plasma Separation Card: a Compelling Alternative to Dried Blood Spots for Quantification of HIV-1 Viral Load

Abstract: Plasma HIV viral load testing is the preferred means of monitoring antiretroviral treatment response. Dried blood spots (DBSs) hold considerable logistical advantages over EDTA samples, but they more frequently misclassify virological failure and have higher limits of detection (LoD). Plasma separation cards (PSCs) may overcome these limitations. Health workers collected EDTA whole blood by venipuncture and 140 μl of finger-prick blood by capillary tube from 53 HIV-infected adults. Capillary blood was immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 31 publications
3
59
4
Order By: Relevance
“…These cards maintain all the comparative advantages of DBS, while providing plasma as a matrix for laboratory assays. A recent study under controlled conditions in South Africa showed that viral load results determined using PSC correlated well with those generated using plasma [15]. Our study aimed at evaluating the performance of the PSC for HIV-1 viral load testing in patients…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…These cards maintain all the comparative advantages of DBS, while providing plasma as a matrix for laboratory assays. A recent study under controlled conditions in South Africa showed that viral load results determined using PSC correlated well with those generated using plasma [15]. Our study aimed at evaluating the performance of the PSC for HIV-1 viral load testing in patients…”
Section: Introductionmentioning
confidence: 88%
“…After drying the specimen on the card, it can be transported under a wide range of environmental conditions to a central testing laboratory. Detailed description of how PSC works is available in a recent publication of Carmona et al (2019).…”
Section: Specimen Collectionmentioning
confidence: 99%
“…It is possible that the use of ELISA assays may have caused a systematic bias, as both ELISA assays showed imprecision with higher levels of CRP. Another potential source of error with DBS samples is changes in haematocrit due to inaccurate volume correction estimates, though dried plasma solutions may mitigate against this [29][30][31]. It is also likely that using the patient's subjective 'self-report' of are will not always distinguish an in ammatory are from an increase of pain due to other causes.…”
Section: Limitationsmentioning
confidence: 99%
“…However, these are more difficult to obtain and prepare on‐site and negate several of the advantages of dried blood spots. An elegant solution could be the plasma separation card which separates plasma and cells from finger or heel prick blood collected by a capillary tube and then blotted onto the card, without the need for centrifugation …”
Section: Pre‐analytic Factors and The “Wrong” Nucleic Acidmentioning
confidence: 99%